Preliminary study on gas separation performance of flat sheet mixed matrix (PVDF/Zeolite) - Sunarti, Abd Rahman; Haron, Gamal Abdalla Suliman; Kanasan, Raj Krishna Roshan; Hasrinah, Hasbullah (IOP Publishing, 2018)
Membrane separation has attracted a lot of attention over the last years mainly due to its separation ability, operational capability and economical viability. Mixed matrix membrane (MMM) combines the superior transport and selectivity properties of inorganic membrane materials and the excellent fabrication properties of organic polymers. This emerging technology can be utilized to purify biogas which can be used in a variety of applications. In this study, flat sheet mixed matrix membranes were synthesized with different percentages of N-Mehtyl-2-pyrrolidone (NMP) as solvent, Polyvinylidene Fluoride (PVDF) as the polymer matrix and zeolite 4A as the dispersed fine particles, membrane A (80: 20: 0), membrane B (80: 18: 2), membrane C (80: 15: 5), and membrane D (75: 15: 10) respectively. The membranes were fabricated using dry/wet phase inversion method. The membrane's performance in terms of permeability and selectivity was examined using the single gas permeation device. The general trend was that, the permeability of the two gases (CO2/CH4) decreased with the increase of the pressure (0.5, 1, 1.5) bar. Membrane D was found to be suitable to separate the pair gas (CO2/CH4) as the permeability was 65623.412, Barrer and 15587.508, Barrer respectively, and its selectivity for was 4.21 at 0.5 bar.